2021
DOI: 10.1155/2021/6661235
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acupuncture on Pregnancy Outcomes of Recurrent Implantation Failure: A Systematic Review and Meta-Analysis

Abstract: Objective. To systematically evaluate the efficacy and safety of acupuncture for patients with recurrent implantation failure (RIF) undergoing in vitro fertilization-embryo transfer (IVF-ET) and hopefully provide reliable guidance for clinicians and patients. Methods. Through searching domestic and foreign medical journals, the literature of randomized controlled trials (RCTs) of acupuncture for RIF undergoing IVF-ET was collected. RevMan 5.3 software was used for meta-analysis and Cochrane’s risk of bias asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Basic research has showed that acupuncture can affect gonadotropin-releasing hormone secretion and the menstrual cycle, and improve the blood flow of uterus ( 15 ). Previous systematic reviews have shown that acupuncture can decrease the rate of pregnancy loss ( 16 ), and there are also studies that have shown that acupuncture can improve fertility outcomes and mental health in both men and women ( 17 , 18 ). Owing to a series of adverse events, unexplained recurrent implantation failure, or the high cost of ART, more patients tend to choose acupuncture as a conservative treatment ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Basic research has showed that acupuncture can affect gonadotropin-releasing hormone secretion and the menstrual cycle, and improve the blood flow of uterus ( 15 ). Previous systematic reviews have shown that acupuncture can decrease the rate of pregnancy loss ( 16 ), and there are also studies that have shown that acupuncture can improve fertility outcomes and mental health in both men and women ( 17 , 18 ). Owing to a series of adverse events, unexplained recurrent implantation failure, or the high cost of ART, more patients tend to choose acupuncture as a conservative treatment ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our study showed that acupuncture was also significantly beneficial in the endometrial thickness and tripleline pattern during FET, indicating that this therapy could improve endometrium receptivity, thus increasing pregnancy rates. It was predicted that hsa-miR-449a, hsa-miR-3135b, and hsa-miR-345-3p might be associated with the mechanisms that acupuncture contributed to endometrium receptivity to prepare for embryo transfer (34); and reviews also reported that acupuncture had effects on endometrial receptivity and pregnancy outcomes of recurrent implantation failure (35,36).…”
Section: Main Findingsmentioning
confidence: 99%
“…However, the conclusions in inconclusive. Even if many systematic reviews and meta-analyses still revealed both positive effects (8)(9)(10)(11)(12)(13)(14)(15) and negative benefits of acupuncture assisting IVF success (16)(17)(18)(19)(20)(21)(22)(23)(24). Different searching databases and literature selection criteria may partly contribute to the unconfirmed results.…”
Section: Introductionmentioning
confidence: 99%